2006
DOI: 10.1136/ard.2006.052548
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms and radiographic osteoarthritis: not as discordant as they are made out to be?

Abstract: Objectives: Joint pain and radiographic osteoarthritis are often discordant. Aim: To investigate this issue more closely by studying the detailed nature of pain and disability, and how this relates to radiographic osteoarthritis. Methods: Population-based study of 819 adults aged >50 years with knee pain. The severity of knee pain, stiffness and disability was measured using a validated scale (the Western Ontario and McMaster Universities (WOMAC) Score) and pain persistence was recorded. Global severity was me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
98
3
10

Year Published

2009
2009
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(117 citation statements)
references
References 32 publications
6
98
3
10
Order By: Relevance
“…OA was defined as the presence of at least one knee with a Kellgren-Lawrence Grade 2 or greater. As described by Duncan et al [10], only one knee per individual, the index knee, was analyzed. In patients with unilateral knee pain, the index knee was the painful knee.…”
Section: Methodsmentioning
confidence: 99%
“…OA was defined as the presence of at least one knee with a Kellgren-Lawrence Grade 2 or greater. As described by Duncan et al [10], only one knee per individual, the index knee, was analyzed. In patients with unilateral knee pain, the index knee was the painful knee.…”
Section: Methodsmentioning
confidence: 99%
“…A number of studies indicate that only half of the patients with radiographic OA feel pain, and that there is a weak correlation between pain severity and radiographic changes (31)(32)(33)(34). Even studies showing significant associations between changes in joint structure and symptoms have found that 51% of the subjects with knee pain for >1 year do not show any typical radiographic joint changes, and that up to 50% of patients with the radiographic changes of OA have no symptoms (35). This suggests that the ability of radiography to distinguish painful and non-painful knees in the general population is limited, possibly because of a lack of sensitivity in detecting structural changes, differences in pain susceptibility, other personal determinants of OA symptoms, and obscure structure/pain relationships (36).…”
mentioning
confidence: 99%
“…A radiographic finding is a standard addition to a clinical review. However, the discrepancy between a radiographic finding in osteoarthrosis and events in a painful knee in the general population (22) has been identified (23) and well documented (24, 25) long ago. According to recent research, agreement between ACR clinical criteria of arthrosis and radiographic findings of arthrosis is low, sensitivity is 41% and specificity 75% (26).…”
Section: Discussionmentioning
confidence: 99%